The Impact of CO2Emissions, Climate Changeand Natural Disasterson AgriculturalProduction in Pakistan (Journal of Asian Development Studies, 2026)
The consistency of agricultural productivity is fundamental to global food safety, but it is increasingly under threat from climate change, natural disasters, and CO2 Emissions. Rising CO2 emissions, along with other natural disasters, alter crop-growingpatterns and the broader climate system, including temperatures. This causes agricultural yields to decline, become more variable, be of lower quality, be less certain, and be lower across the board. The primary objective of this research is to examine the relationships among climate change, natural disasters, CO2 emissions, and food safety, with an emphasis on their effects on crop yield quality. We used secondary time-series data from 2000 to 2024 and employed econometric techniques, including the Correlation Matrix and the ARDL model, to estimate these relationships. The findings reveal that decoupled changes in the period and level of temperature, rainfall, and the occurrence of natural disasters are outcomes of climate change and CO2 emissions, and these negatively affect agricultural production. which acts unsustainably on agricultural production. The study suggests global cooperation and strong policy initiatives to control climate change and reduce CO2 emissions, as the UN’s SDG 13 emphasises the urgent need for a global response to curb the release of greenhouse gases, particularly CO2.